3x+6=9(x+9)

Simple and best practice solution for 3x+6=9(x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+6=9(x+9) equation:


Simplifying
3x + 6 = 9(x + 9)

Reorder the terms:
6 + 3x = 9(x + 9)

Reorder the terms:
6 + 3x = 9(9 + x)
6 + 3x = (9 * 9 + x * 9)
6 + 3x = (81 + 9x)

Solving
6 + 3x = 81 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
6 + 3x + -9x = 81 + 9x + -9x

Combine like terms: 3x + -9x = -6x
6 + -6x = 81 + 9x + -9x

Combine like terms: 9x + -9x = 0
6 + -6x = 81 + 0
6 + -6x = 81

Add '-6' to each side of the equation.
6 + -6 + -6x = 81 + -6

Combine like terms: 6 + -6 = 0
0 + -6x = 81 + -6
-6x = 81 + -6

Combine like terms: 81 + -6 = 75
-6x = 75

Divide each side by '-6'.
x = -12.5

Simplifying
x = -12.5

See similar equations:

| 7(4x+7)=6(1+x)-1 | | 2e^3x-2=7 | | C-13=5(3) | | 40=8(n-2) | | -5(8x+4)=-140 | | c=49.99-.25*49.99 | | 4[8-(-9x-1)]=180x+52 | | 3y-10x=-45 | | 5(4x-3)=15 | | x=(4y-9)(6y-7) | | 5+x=4(8) | | y+8=3(x+15) | | 70619.542=2*3.14*1303.21+2*3.14*36.1*h | | 2+4sinx=0 | | 422.67=c+.15c | | -(-4x+10-8y)= | | 8+3m-4=6m+9-2m | | 4x-5+x=7+5x-2 | | y+8=3(x+5) | | 3n-2(n+10)=n-20 | | 2w+6x-14y+8w+9x+6y= | | 81650.99=2*3.14*r^2+2*3.14*287.8*r | | 2m+1-4=-2m-3 | | 4(2x+1)=5x | | 7t-22=26+t | | (S-9)(s-1)=0 | | r+9r=-8 | | 18j-5=3(6j-2) | | 150=c+.18c | | 4x+(-8x)= | | a+75=-1+9 | | 81650.99=2*3.14*2*r+2*3.14*r*287.9 |

Equations solver categories